SIMULATION MODEL DESIGN TO DETERMINE NUMBER OF FIXED COURIER IN CARGO SERVICE PROVIDER COMPANY - KURNIA NIM 13414007, DAVIN
Rapid growth of online businesses in Indonesia has been bringing a good potency for Logistics Service Provider companies, one of which is Company X. Currently, the operational activities of Company X are running well with the total courier operational cost equals to IDR 18,540,000 per month. However, Company X is trying to keep this cost down so then Company X make an innovation to apply sharing economy concept. This concept in its operational process will involve freelance courier, in addition to the fixed courier that the company does have currently. The problem that arises is how to determine number of fixed courier to have the total courier operational cost minimum. In this research, we will use dynamic system simulation to solve the problem. This is because the system being reviewed has characteristics of dynamics, especially regarding time demand appears, distance of demand, availability of fixed courier, availability of freelance courier, and compensation fee which will be given. Simulation will be done twice using hypothetical data and real data. By using hypothetical data, simulation is used for validation. Meanwhile, solving the problem in this research will use real data based on historical data from Company X. Simulation experiment using hypothetical data produce logical and valid output so simulation will be continued using real data. Simulation using real data resulted in a solution consisting of 3 fixed couriers. This solution generate total courier operational cost equals to IDR 9,300,000 per month so as to get total courier operational cost saving of IDR 9,240,000 per month or 49,84% from existing condition.